Interpretation of core ion cyclotron emission driven by sub-Alfvénic beam-injected ions via magnetoacoustic cyclotron instability. (4th July 2019) - Ochoukov, R.; McClements, K.G.; Bilato, R.; Bobkov, V.; Chapman, B.; Chapman, S.C.; Dendy, R.O.; Dreval, M.; Faugel, H.; Noterdaeme, J.-M.; Salewski, M.; Weiland, M.
Abstract: Core ion cyclotron emission (ICE) signals have recently been observed in beam-heated plasmas on several tokamaks. In this manuscript we present experimental evidence in support of core ICE being generated by the magnetoacoustic cyclotron instability (MCI), itself driven by the velocity-space inversion of sub-Alfvénic beam-injected ions. The observed core ICE amplitude evolution in beam-heated plasmas is consistent with the MCI and is a result of competition between the beam ion fraction build-up (which increases the instability growth rate) and the slowing down of the dominant beam ion velocity component (which stabilizes the MCI). The oblique propagation angle is constrained to lie in the range 75–78°, where the lower bound is governed by the fast wave reabsorption losses on plasma electrons and bulk ions and the upper bound is governed by the experimentally observed ICE amplitude growth time. Although the oblique MCI is a local theory and does not provide information on the radial mode localization, the calculated instability growth rates are broadly consistent with the observed dynamics of the core ICE amplitude on the ASDEX Upgrade tokamak.